(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Cybersport events are a cutting-edge global phenomena. Because of this, the purpose of this study is to identify the potential of cybersport as a substitute for diversifying tourism events in Guayaquil, Ecuador. It was suggested to examine the circumstances surrounding cybersport events and how visitors view them in the chosen city within the methodological framework of an exploratory-descriptive scope. 384 attendees at cybersport events (possible tourists) who used player community networks and video game rooms around Latin America were given a survey. A questionnaire that was made available online for six months in order to allow for future analysis served as the data collection tool. The foremost discoveries in terms of quality execution of the occasion, discernment of the occasion, goal picture, and fulfillment uncovered four imperative pointers related. Occasion staff, occasion climate, neighborliness, and great sentiments approximately live participation must be taken into thought whereas planning a palatable encounter to coordinated into cybersport into the city’s tourism offerings. Participants too communicated their eagerness to return to the city within the future. These comes about contribute to growing the logical writing on the assessment and administration of cybersport occasions for other creating cities and nation